Greatly improved HER electrocatalytic activity by the composite of CoSe2 and N, S-dual doped graphitic carbon. (21st May 2019) - Tong, Jinhui; Li, Tao; Bo, Lili; Li, Wenyan; Li, Yuliang; Zhang, Qi
Abstract: Several composite catalysts were facilely fabricated by hydrothermal supporting CoSe2 on N, S dual-doped graphitic mesoporous carbon (SDGC) synthesized by pyrolyzing thiocarbamide and in-situ formed phenolic resin. The synthesized CoSe2 /SDGC composites were characterized to have mesoporous structure distributed on the carbon matrix covered with the sphere like aggregates of CoSe2 . Their electrocatalytic performances were evaluated by hydrogen evolution reaction (HER) in 0.5 M H2 SO4 . The results have shown that the as-prepared catalysts exhibited highly improved electrocatalytic activities for HER compared with the pristine CoSe2 and SDGC. Especially, the composite CoSe2 /SDGC-60 with the optimized ratio of CoSe2 to SDGC has exhibited the highest electrocatalytic activity. The catalyst has obtained the lowest overpotential and Tafel slope of 203 mV (at 10 mA/cm 2 ) and 58 mV/dec, respectively. It also showed impressive durability against 0.5 M H2 SO4 and the electrocatalytic activity hardly decreased even after 5000 cycles. Highlights: N, S dual-doped graphitic mesoporous carbon was simply prepared. The obtained carbon with high surface area, graphitization and pyridinic nitrogen. CoSe2 was hydrothermally wrapping on the as-prepared carbon. The as-prepared composite is most efficient for HER in acidic solution.